(untitled) (Global Journal of Management and Business Research, 2016)
Purpose: The purpose of this paper is to examine the effect of individual-based, firm-based, and market factors on job retention, basing its hypotheses on human capital theory and signalling models. Design/methodology/approaches: Cluster sampling method was utilized for this research. This research is conducted to determine the employee retention factors in selected industries. Upon selecting the 4 industry and 4 organizations, the designed questionnaires were equally distributed to all the 4 organization with 50 questionnaires for each. Again, from many organizations in one industry we select the most accessible organization and distributed the questionnaires to 50 respondents. This would be the applicable for all other 3 industries and organization. Findings: Growth and development, working culture and environment, remuneration, recognition and empowerment are motivating factors in an organization that are primary causes of job satisfaction leading to retention.